THEMATIC AND LINGUISTIC FEATURES OF TOLIBAY QABULOV’S POETRY - Tasbaeva, Dilyarom (International Conference on Science, Education & Law, 2026)
This article analyzes the poetry of Tolibay Qabulov, focusing on its themes, language, and cultural significance. It shows that his works reflect a strong connection with the people, express national identity, and combine simple language with deep meaning. In addition, his poetry highlights themes of homeland, human values, and continuity, while also demonstrating musical qualities through song-like structure. Overall, his work represents both a literary and cultural legacy.